STRATEGI PENGEMBANGAN TABUNGAN EASY MUDHARABAH PADA BANK SYARIAH INDONESIA KANTOR CABANG SAMBAS - Sony (Lunggi Journal, 2024)
The research conducted is a field research conducted at Bank Syariah Indonesia, Sambas Branch Office, Sambas District, Sambas Regency, West Kalimantan. The data obtained in this research were gathered from interviews and documentation during the researcher’s time at the Bank Syariah Indonesia Sambas Branch Office. The method used in the data analysis is SWOT analysis, which is employed to analyze the strategy for the development of mudharabah savings products at the Bank Syariah Indonesia Sambas Branch Office. The results of this study indicate that the mudharabah contract used for savings products at Bank Syariah Indonesia Sambas Branch Office is the mudharabah muthalaqah type. Mudharabah muthalaqah is a cooperation contract in which the managing party is given the freedom to manage the capital provided by the capital owner for any business. The capital owner will then receive profits through profit sharing or nisbah. The development strategy implemented by Bank Syariah Indonesia Sambas Branch Office includes improving product quality, maintaining product strengths, conducting direct outreach to the community, utilizing internet media for product promotion, and maintaining the company’s good reputation.